Kasus Pneumonia dengan Riwayat Tuberkulosis, Kambuhnya Tuberkulosis, Paru yang Hancur, Sopt, Hipokalemia, Cor Pulmonale, dan Hipertensi Pulmonal - Fachriyah, Alfi Sri; Santosa, Budi (Syntax Literate, 2025)
Pneumonia is an inflammation of the lung parenchyma caused by microorganisms such as bacteria, viruses, fungi, and parasites. Patients with relapsing pulmonary tuberculosis (TB) pneumonia can experience complications such as Destroyed lung, Post-Tuberculosis Obstruction Syndrome (SOPT), Cor pulmonary and pulmonary hypertension. Such a condition is suspected due to a history of chronic tuberculosis is also a comorbid condition in these patients. One case has been reported in the hospital Sumber Waras with the main complaint of chest pain accompanied by tightness 1 week before hospital admission in a 42-year-old man whose diagnosis was established based on history, physical examination, and supporting examinations. Given treatment both pharmacologically and non-pharmacologically.